Examining the racial-ethnic continuum and perceptions of police misconduct - Graziano, Lisa M. (Policing and society, 2019)
Some research suggests a racial-ethnic hierarchy exists as to perceptions of police, with African-Americans exhibiting the most negative attitudes, Whites the most positive, and Hispanics holding more intermediate attitudes. Other findings regarding Hispanics are less consistent and little study has been made of Asians. This study further tests the premise for such a hierarchy by examining the views of both Hispanics and Asians alongside those of African-Americans and Whites as they relate to police misconduct. Partial support for a hierarchy of attitudes was found, with Hispanics exhibiting the hypothesised intermediate attitudes. While race remained an important factor for explaining African-Americans’ attitudes, other factors ultimately better explained Hispanics’ attitudes. The attitudes of Asians were indistinguishable from those of Whites. These findings suggest the experiences of racial-ethnic groups widely vary and the premise of a racial-ethnic continuum may be too simplistic for understanding the attitudes of Asians and Hispanics.